The influence of stretcher height on the mechanical effectiveness of rowing - Caplan, N.; Gardner, T. N. (Journal of Applied Biomechanics, 2005)
The aim of the present study was to determine the effect of varying the height of the foot stretcher on the mechanical effectiveness of rowing. Ten male university level rowers rowed maximally for 3 minutes 30 seconds on a modified Concept 2 rowing ergometer. Each participant completed one trial at three foot stretcher heights. Position 1 was the original Concept 2 stretcher position, with Position 2 being located 5 cm and Position 3 being 10 cm above the original position and in the same orientation. Pull force and velocity were measured, and mean power generated by the rowers was calculated for each stroke. It was shown that in all three stretcher positions, mean power per stroke decreased as a function of time during the trial, confirming the fatiguing effects of the task. Although mean power per stroke did not differ significantly between stretcher positions at the start of the trial, p = 0.082, a significant difference was observed between the original stretcher position and Positions 2 and 3 at the end of the trial, p < 0.05. The lowest decline in mean power occurred in the highest stretcher position. It is suggested that this improvement in effectiveness is due to a reduction in the active downward vertical forces applied to the foot stretchers which does not contribute to forward propulsion, and thus a reduction in energy waste during each stroke. It was hypothesized that further raising the stretchers will continue to lead to an improvement in effectiveness until the optimum stretcher height is reached, above which effectiveness will be reduced.